Kinematic effects of unilateral TKA on the contralateral knee in Chinese patients with advanced osteoarthritis: a prospective gait analysis study - Wang, Haibo; Duan, Wenhao; Dang, Xiaodong; Chen, Zhenxian; Peng, Yinghu; Yao, Shuxin; Zhang, Weijie; Ma, Jianbing (Frontiers in Bioengineering and Biotechnology, 2024)
Patients with knee osteoarthritis (OA) who receive unilateral total knee arthroplasty (TKA) often report reduced pain and enhanced function in the untreated knee, yet the kinematic mechanisms are not fully understood. Our study aimed to clarify these effects through a gait analysis of the untreated knee following unilateral TKA. This study enrolled 118 end-stage OA patients with varus deformity scheduled for TKA, categorized into the contralateral osteoarthritis group (Contra-OA), consisting of patients with end-stage OA in both knees requiring surgical treatment, and the contralateral TKA group (Contra-TKA), which included patients who had undergone TKA on one knee and had endstage OA in the untreated knee awaiting surgery. Kinematic data of the knee joint during treadmill walking were collected using the Opti_Knee gait analysis system, and a comparative analysis was conducted. The Contra-TKA group exhibited improvements in step length, anterior-posterior translation, range of motion, vertical translation, and internal-external rotation compared to the Contra-OA group (p-values ranging from 0.0013 to 0.0463). Notable differences in flexion-extension angles and abduction/adduction rotation were also observed (p=0.0013 and 0.0166, respectively). At the initial contact (IC), obvious differences in internal-external rotation, anterior/posterior translation, and vertical translation were noted. At the opposite toe-off (OT), significant differences in internal-external rotation. At the tibia vertical (TV) moment, significant differences were observed in all three translation indicators of joint translation. At other pivotal gait cycle points, vertical and anterior/posterior translations in Contra-TKA group continued to exhibit more meaningful decrease. Collectively, these findings underscore the protective kinematic effects of TKA on the untreated contralateral knee, indicating an improved biomechanical adaptation following TKA surgery. In summary, the study's findings indicate that unilateral TKA imparts kinetic effects on the untreated contralateral knee, as evidenced by significant improvements in key gait parameters. These enhancements, observed at both initial contacts and throughout the gait cycle, suggest a positive biomechanical support post-TKA, might contribute to better gait efficiency and reduced load on the contralateral untreated knee.